PID Controller Design for Heating Furnace Temperature Based on Bat Algorithm (BA) - Machrus Ali; Budiman Budiman (Merdeka Malang University, 2023)
A furnace is a tool for heating materials, oil, and others. Furnaces use gas, coal, and oil as fuel. Temperature is the main parameter that needs to be controlled to remain stable, and precise and improve fuel efficiency. As technology develops, several methods can be used to control temperatures that are more reliable than conventional controls. The technology is a Proportional Integral Derivative (PID) controller. PID controllers have been proven and widely used in the industry, but determining the gain of the PID value is still not accurate. This can affect temperature stability, and slow response to reach the desired set point. Therefore, it is necessary to optimize the control system. Optimizing by looking for a better PID gain value with the artificial intelligence tuning method. The Artificial Intelligence method is Bat Algorithm(BA). The simulation results and discussion show that the best design is PID-BA with an overshoot of 0.0429, non undershoot, and the fastest settling time of 16.9 seconds